Medical cannabis for the treatment of comorbid symptoms in children with autism spectrum disorder: An interim analysis of biochemical safety - Stolar, Orit; Hazan, Ariela; Vissoker, Roni Enten; Kishk, Ibrahim Abu; Barchel, Dana; Lezinger, Mirit; Dagan, Adi; Treves, Nir; Meiri, David; Berkovitch, Matitiahu; Kohn, Elkana; Heyman, Eli (Frontiers in Pharmacology, 2022)
Background: Autistic Spectrum Disorder (ASD) is a common neurodevelopmental disorder and no effective treatment for core symptoms is currently available. The present study is part of a larger clinical trial assessing effects of cannabis oil on autism co-morbidities. Objectives: The aim of the present study was to assess safety of a CBD-rich oil treatment in children and adolescents with ASD. Methods: Data from 59 children and young adults (ages 5-25 years) from a single-arm, ongoing, prospective, open-label, one center, phase III study was analyzed. Participants received Nitzan Spectrum® Oil, with cannabis extracts with a CBD:THC ratio of 20:1, for six months. Blood analysis was performed before treatment, and after 3 months. CBC, glucose, urea, creatinine, electrolytes, liver enzymes (AST, ALT, GGT), bilirubin, lipid profile, TSH, FT4, thyroid antibodies, prolactin, and testosterone measurements were performed at baseline, before treatment and study midpoint, after three months. Results: 59 children were followed for 18± 8 weeks (mean ±SD). Mean total daily dose was 7.88±4.24 mg/kg body weight. No clinically significant differences were found in any analytes between baseline and 3 months follow up. LDH, FT4, and TSH were all significantly higher before treatment compared to after 3 months, however, all values were within normal range. A comparison of the group with additional medications (n=14) to those who received solely medical cannabis (n=45) showed no difference in biochemical analysis, including liver enzymes, except change in potassium which was significantly higher in the group that did not receive additional medications compared to those receiving drug therapy (p=0.04). A comparison of patients receiving high compared to low dose cannabis oil, showed no significant difference between groups, except for mean change of total protein, which was significantly higher among patients receiving high dose compared a low dose of CBD, and mean change in number of platelets, that was significantly lower among patients who received high dose of CBD compared to low dose of CBD (p=0.0007). However, both changes lack clinical significance. Conclusions: CBD-rich cannabis oil (CBD: THC 20:1), appears to have a good safety profile. Long-term monitoring with a larger number of participants is warranted.